Predictors of education and utilization of adolescent-friendly health services among youth in Kumbungu district, Ghana - Martin Nyaaba Adokiya; Francis Kronzu Cudjoe; Vida Nyagre Yakong (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This paper assessed factors affecting adolescent-friendly health services (AFHS), education and utilization among youth (10-19 years) in Kumbungu district, Ghana. Design/methodology/approach - The study used a cross-sectional design involving 416 adolescents from households using a random sampling technique. The authors collected data on sociodemographic characteristics, education and utilization of AFHS using a semi-structured questionnaire between June and September 2017. Logistic regression models were used to determine the factors associated with AFHS education and utilization. Findings - Of the 416 adolescents interviewed, 66% were between 15 and 19 years. Half (50%) of the adolescents received AFHS education, 54% utilized existing services and 85% knew about health challenges. Females (aOR = 0.64; p = 0.031) were less likely to receive AFHS education compared to males. Muslims (aOR = 0.21; p < 0.001) were less likely to utilize AFHS compared to Christians. Adolescents with primary (aOR = 6.65; p = 0.020), junor high school (JHS) (aOR = 10.66, p = 0.079) or senior high school (SHS) (aOR = 1.04; p = 0.954) education were more likely to utilize AFHSs compared to those with no education. Originality/value - This study reports a moderate level of education and the utilization of adolescent health services. Sex, religion and education are the key predictors of AFHS education and utilization. This study contributes to the understanding of adolescent health services and the foundation for future studies. It may be used for the planning of adolescent health service programs in disadvantaged settings.